Universitarios madrileños en Facebook : vacío y apatía en la red social - Martínez Valerio, Lizette (Universidad de Chile. Instituto de la Comunicación e Imagen, 2016)
Since the first online social networks appeared in the early XXI century, these platforms have not stopped growing, and now are part of millions of people’s daily life worldwide, mainly young people. However, do we know what they are sharing in these spaces? This research studies the activity on Facebook of students from Madrid universities. The data presented here are the result of the analysis within the online ethnography. The findings show that young people seem to have no problema with sharing their age or place of origin, but are reluctant to disclose more personal issues such as sexual orientation. But most important es that while interactivity is one of the hallmarks of these new media, users of this social network spend a considerable amount of time just watching others without doing anything else.